The thermo-optical properties of some solar absorbers - Kunç, Seref (My University, 1987)
The solar absorbers in the utilization of solar energy are selected according to their thermooptical properties, environmental stability and fabrication costs. At low temperature applications, a suitable black dye may be used. We measured the dye used in Turkey and found that ithad an ?s value of 0.88 and ?{lunate}80 of 0.80, and graphite powder, which was more stable to environmental condition and temperature, had ?s value of 0.95 and ?{lunate}80 of 0.93. At medium temperature application low cost black nickel coating may be preferable and their ?s values were varied between 0.080 and 0.92 and ?{lunate}100 values between 0.08 and 0.50 depending on the coating variables. Black chromium coating may be also used for this purpose and they are stable up to 400°C depending on the preparation processes. Their ?s values varied between 0.88 and 0.96 and ?{lunate}100 between 0.080 and 0.22. For high temperature applications, textured chromium surfaces prepared by PVD technique have a promising future and have ?s values of 0.80-0.90 and ?{lunate}100 values of 0.10-0.30 depending on the coating variable. The dependence of thermo-optical properties of the above surfaces to temperature were discussed. As we know ?s values do not depend upon temperature. The variation of ?{lunate} with temperature were calculated from near normal hemispherical reflectance data which has some effect on the design of solar collectors. © 1987.